Aluminum oxide interface cross-linked and rubber powder volume rejection mediated high-thermal-conductivity ethylene propylene diene monomer composite material and preparation method thereof
Through the method of alumina interface crosslinking and mediating glue powder volume repulsion, high thermal conductivity EPDM rubber composites are prepared, which solves the problems of low thermal conductivity of existing thermal interface materials and difficult to recycle waste tire rubber powder, and achieves the goal of efficient heat transfer and green environmental protection.
Patent Information
- Application Number
- CN202510088905.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-08
AI Technical Summary
The existing thermal interface materials have problems such as high thermal filler content, high thermal resistance and low thermal conductivity of heterogeneous interfaces. At the same time, it is difficult to effectively recycle and utilize waste tire glue powder, which violates the concept of green and sustainable development.
High thermal EPDM rubber composites are prepared by mediating interfacial cross-linking of alumina and volume repulsion of rubber powder. The method includes coating the spherical alumina surface with organic layer, and performing a reversible covalent cross-linking reaction with anhydride ethylene propylene tereum rubber, adding waste rubber powder and carbon nanotubes, and preparing the composite material by high temperature hot pressing.
It improves the mechanical properties and thermal conductivity of EPDM rubber, forms an effective thermal conductivity network, reduces phonon scattering, improves heat transfer efficiency, and has the characteristics of high thermal conductivity and green environmental protection.
Smart Images

Figure CN119775679A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermal conductive rubber, and in particular to a method for preparing a high thermal conductive EPDM rubber composite material mediated by aluminum oxide interface cross-linking and rubber powder volume exclusion. Background Art
[0002] During the use of electronic equipment, there is serious heat accumulation, which affects the operational stability and endangers its service life. At the same time, it will also cause safety hazards of varying degrees. In order to cater to the continuous updating and iteration of electrical equipment, it is urgent to solve the problem of heat dissipation of electronic equipment. Thermal interface materials play an important role in thermal management because they can significantly reduce the contact thermal resistance between heat dissipation devices and heating devices. Among them, rubber-based elastic thermal interfaces can meet the comprehensive needs of thermal management due to their advantages such as flexibility and flexibility. The main chain of EPDM rubber is composed of chemically stable saturated hydrocarbons, and only contains unsaturated double bonds in the side chains. It can be grafted with monomers with higher reaction activity, which is convenient for subsequent modification. Therefore, it can be used as a candidate material for elastic thermal interface materials.
[0003] In addition, the increasing amount of waste tires has put serious pressure on the global ecological environment. Waste tires are hazardous solid wastes, known as "black pollution". Improper disposal will seriously affect human health and endanger the safety of the ecological environment. The current landfill incineration and other methods run counter to the concept of green and sustainable development, but waste tire rubber powder can only be used for secondary production, and high-value recycling is rare, which cannot meet the requirements of green and sustainable development. In order to solve the problems of high content of thermal conductive fillers, high thermal resistance of heterogeneous interfaces, and low thermal conductivity in traditional thermal interface materials and at the same time recycle waste rubber powder at a high value, it is of potential value to combine rubber-based elastic thermal interface materials with waste rubber powder.
[0004] Chinese patent CN202110922167.3 discloses a method for preparing insulating thermally conductive carbon fibers for thermal interface materials, wherein SiO2 sol is prepared by a sol-gel method, and then carbon fibers and SiO2 are mixed, SiO2 can be easily and evenly coated on the surface of carbon fibers, and SiO2 is converted into SiC or Si3N4 under high temperature conditions, and the coated carbon fibers are evenly mixed with liquid silicone rubber, and an electric field is applied to achieve directional orientation of carbon fibers to prepare highly thermally conductive and soft thermal interface materials. Chinese patent CN202411046471.6 discloses a method for preparing graphene thermal interface materials, wherein graphite paper is graphitized, and then shear-intercalation expansion-peeling is performed to form a graphene film, and finally immersed in a polymer solution to form a modified layer to obtain the graphene thermal interface material. However, the above materials are all thermosetting thermal interface materials that cannot be recycled, and are difficult to industrialize due to high costs. Chinese patent CN202410841566.0 discloses a method for preparing a grafted silicone-based thermal interface material, wherein the hydrogenated silicone oil is grafted to obtain a modified silicone oil, and then vinyl silicone oil, thermal conductive filler and coupling agent are added and mixed evenly to obtain a grafted silicone-based thermal interface material. However, this material is prone to leakage and volatility. Therefore, it is still challenging to use a method that is easy to scale, low-cost and efficient to study and prepare high thermal conductivity elastic thermal conductive materials. Summary of the invention
[0005] The purpose of the present invention is to provide a high thermal conductivity EPDM rubber composite material mediated by aluminum oxide interfacial crosslinking and rubber powder volume exclusion and a preparation method thereof in view of the deficiencies in the prior art. The invention is characterized in that the surface of spherical aluminum oxide (Al2O3) is treated to form a stable organic coating layer by complexing with organic phosphoric acid and iron ions while regulating the reaction time and deposition environment, and an organic acid anhydride is grafted onto the EPDM molecular chain under high temperature shearing to prepare anhydride EPDM rubber; organic modified aluminum oxide and anhydride EPDM are blended on a double-roll mill, and under the catalytic action of zinc acetate, the phosphoric acid hydroxyl groups on the surface of Al2O3 form a reversible bond with the anhydride groups on the EPDM molecular chain. Carboxyl ester bond, while zinc acetate provides ionic crosslinking; further adding different proportions of waste rubber powder and carbon nanotubes (CNTs), high thermal conductivity EPDM rubber composite materials are prepared by high temperature hot pressing. On the one hand, the presence of dynamic reversible crosslinking bonds improves the mechanical properties of EPDM rubber. On the other hand, due to the volume exclusion effect of waste rubber powder, Al2O3 and CNTs are concentrated in the EPDM matrix and selectively positioned in the edge area, and fillers of different dimensions bridge each other to form a three-dimensional thermal conductive network. This structure can provide an effective, continuous and large number of thermal conductive paths, reduce phonon scattering, make heat transfer more rapid and efficient, and have high thermal conductivity.
[0006] The object of the present invention is achieved by the following technical scheme, wherein the raw material fractions are all mass fractions unless otherwise specified.
[0007] The main raw materials of a high thermal conductivity EPDM rubber composite material mediated by aluminum oxide interfacial crosslinking and rubber powder volume exclusion are composed of the following components, calculated by weight: A high thermal conductivity EPDM rubber composite material mediated by aluminum oxide interfacial crosslinking and rubber powder volume exclusion and a preparation method thereof, characterized in that the main raw material of the rubber is composed of the following components, calculated by mass fraction: EPDM 100 parts Waste rubber powder (WRP) 100-200 copies Spherical alumina (Al2O3) 10-25 parts Carbon nanotubes (CNTs) 1-6 parts 1-4 parts of organic phosphoric acid 2-6 parts of organic anhydride 2-6 parts of iron salt Wherein, the organic phosphoric acid is any one of phytic acid, propyl phosphoric acid, phenyl phosphoric acid, trimethyl phosphoric acid, and acryloyl isopropyl phosphoric acid; The organic acid anhydride is any one of itaconic anhydride, maleic anhydride and succinic anhydride; The iron salt is any one of ferric chloride, ferric sulfate and ferric nitrate.
[0008] The high thermal conductivity EPDM rubber composite material mediated by aluminum oxide interface cross-linking and rubber powder volume exclusion and the preparation method thereof comprise the following steps: S1: Surface organic layer coating of spherical aluminum oxide Add 10-25 parts of spherical aluminum oxide (Al2O3) to 200-350 parts of a mixed solution of deionized water and isopropanol in a volume ratio of 7:3, and ultrasonicate for 1 hour to make it uniformly dispersed, and then continue to mechanically stir it at a uniform speed. Dilute 1-4 parts of organic phosphoric acid with 10-40 parts of deionized water, add it to the above Al2O3 dispersion, make the solution pH value just 3, and stir vigorously for 5 minutes. Dissolve 2-6 parts of iron salt in 20-60 parts of deionized water to prepare a solution, add it to the above dispersion, and stir slowly at a uniform speed for 1 hour to make it uniformly coated. Vacuum filter, wash, and dry at 60℃ for 24 hours to obtain spherical Al2O3 coated with an organic layer.
[0009] S2: Preparation of anhydride EPDM rubber Add 100 parts of EPDM into an internal mixer at 170°C and 60 r / min, and mix for 3 minutes. Then add 2-6 parts of organic anhydride and 0.1 part of diisopropylbenzene peroxide (DCP) into the EPDM and mix evenly. Continue to react for 5-15 minutes. Finally, add 2 parts of zinc acetate and mix for 3 minutes. Take out the product and cool it to room temperature to obtain anhydride EPDM.
[0010] S3: Preparation of high thermal conductivity EPDM rubber composites 100 parts of anhydride EPDM were added to a two-roll mill and mixed at room temperature. After 5 minutes, the modified spherical alumina prepared by S1 was added and mixed for 15 minutes. Then, it was transferred to an internal mixer and 100-200 parts of waste rubber powder (WRP) were added and mixed at 150°C and 60 r / min for 5 minutes. Then, 1-6 parts of carbon nanotubes (CNTs) were added and mixed for another 10 minutes. Finally, it was hot pressed at 150°C and 15 MPa for 5-20 minutes to obtain a high thermal conductivity EPDM rubber composite material mediated by alumina interfacial crosslinking and rubber powder volume exclusion.
[0011] The invention has the following advantages: the thermal conductive filler and the rubber matrix belong to a heterogeneous interface, the interface bonding ability is poor and there is a high interface thermal resistance. On the other hand, the thermal conductive filler has poor dispersibility in the rubber matrix, and its own high intrinsic thermal conductivity is difficult to fully exert, but the high filler content will affect the mechanical properties, flexibility and elasticity of the rubber. The invention uses a complex of organic phosphoric acid and iron salt to stably and controllably coat the zero-dimensional spherical alumina, the purpose of which is to reduce the interface thermal resistance, and then it undergoes a reversible covalent cross-linking reaction with anhydride-treated ethylene propylene rubber to form a carboxyl ester bond, so that more effective heat conduction paths are formed in the ethylene propylene rubber. At the same time, the zero-dimensional filler spherical alumina and the one-dimensional filler carbon nanotubes are mutually bridged, and under the volume exclusion of the rubber powder, they are concentratedly dispersed inside the ethylene propylene rubber and selectively positioned in the boundary area to form macroscopic and microscopic heat conduction paths, establish a rich dynamic covalent cross-linking network, thereby reducing phonon scattering and improving heat transfer efficiency. The preparation method is simple and efficient, has high thermal conductivity, is green and pollution-free, and has significant advantages. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 Scanning electron microscope images of the microstructure of spherical alumina before and after modification.
[0013] Figure 2 Schematic diagram of the network structure of EPDM rubber composite material. DETAILED DESCRIPTION
[0014] The present invention is further described below through specific examples. It should be noted that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make non-essential improvements and adjustments to the present invention based on the contents of the present invention described above. Example
[0015] Surface organic layer coating of spherical alumina Add 10 parts of spherical aluminum oxide (Al2O3) to a mixed solution of 200 parts of deionized water and isopropanol in a volume ratio of 7:3, and disperse it evenly by ultrasonication for 1 hour, and then continue to stir it mechanically at a uniform speed. Dilute 1 part of phytic acid with 10 parts of deionized water, add it to the above Al2O3 dispersion, make the solution pH value just 3, and stir vigorously for 5 minutes. Dissolve 2 parts of ferric chloride in 20-60 parts of deionized water to prepare a solution, add it to the above dispersion, and stir slowly at a uniform speed for 1 hour to make it uniformly coated. Vacuum filter, wash, and dry at 60℃ for 24 hours to obtain spherical Al2O3 coated with an organic layer.
[0016] Preparation of anhydride ethylene propylene diene monomer rubber 100 parts of EPDM were added into an internal mixer at 170°C and 60 r / min for 3 min, then 2 parts of itaconic anhydride and 0.1 parts of diisopropylbenzene peroxide (DCP) were added into the EPDM and mixed evenly, and the reaction was continued for 8 min. Finally, 2 parts of zinc acetate were added and internal mixer was performed for 3 min. The product was taken out and cooled to room temperature to obtain anhydride EPDM.
[0017] Preparation of high thermal conductivity EPDM rubber composites 100 parts of anhydride EPDM were added to a two-roll mill and mixed at room temperature. After 5 minutes, modified spherical alumina was added and mixed for 15 minutes. Then, it was transferred to an internal mixer, and 100 parts of waste rubber powder (WRP) was added and mixed at 150℃ and 60 r / min for 5 minutes. Then, 2 parts of carbon nanotubes (CNTs) were added and mixed for 10 minutes. Finally, it was hot-pressed at 150℃ and 15 MPa for 8 minutes to obtain a high thermal conductivity EPDM composite material mediated by alumina interfacial crosslinking and rubber powder volume exclusion. According to the test, the tensile strength of the EPDM composite material is 1.12 MPa, the elongation at break is 368%, and the thermal conductivity is 1.43 W / mK. Example
[0018] Surface organic layer coating of spherical alumina Add 15 parts of spherical aluminum oxide (Al2O3) to a mixed solution of 250 parts of deionized water and isopropanol in a volume ratio of 7:3, and disperse it evenly by ultrasonication for 1 hour, and then continue to stir it mechanically at a uniform speed. Dilute 1.5 parts of phytic acid with 15 parts of deionized water, add it to the above Al2O3 dispersion, make the solution pH value just 3, and stir vigorously for 5 minutes. Dissolve 3 parts of ferric chloride in 30 parts of deionized water to prepare a solution, add it to the above dispersion, and stir slowly at a uniform speed for 1 hour to make it evenly coated. Vacuum filter, wash, and dry at 60℃ for 24 hours to obtain spherical Al2O3 coated with an organic layer.
[0019] Preparation of anhydride ethylene propylene diene monomer rubber 100 parts of EPDM were added into an internal mixer at 170°C and 60 r / min for 3 min, then 2 parts of itaconic anhydride and 0.1 parts of diisopropylbenzene peroxide (DCP) were added into the EPDM and mixed evenly, and the reaction was continued for 10 min. Finally, 2 parts of zinc acetate were added and internal mixer was performed for 3 min. The product was taken out and cooled to room temperature to obtain anhydride EPDM.
[0020] Preparation of high thermal conductivity EPDM rubber composites 100 parts of anhydride EPDM were added to a two-roll mill and mixed at room temperature. After 5 minutes, modified spherical alumina was added and mixed for 15 minutes. Then it was transferred to an internal mixer, 150 parts of waste rubber powder (WRP) was added and mixed for 5 minutes at 150℃ and 60 r / min, and then 2 parts of carbon nanotubes (CNTs) were added and mixed for 10 minutes. Finally, it was hot-pressed at 150℃ and 15 MPa for 8 minutes to obtain a high thermal conductivity EPDM composite material mediated by alumina interfacial crosslinking and rubber powder volume exclusion. According to the test, the tensile strength of the EPDM composite material is 1.29 MPa, the elongation at break is 321%, and the thermal conductivity is 1.61 W / mK. Example
[0021] Surface organic layer coating of spherical alumina 20 parts of spherical aluminum oxide (Al2O3) were added to 300 parts of a mixed solution of deionized water and isopropanol in a volume ratio of 7:3, and ultrasonicated for 1 h to make it uniformly dispersed, and then continuously mechanically stirred at a uniform speed. 2 parts of trimethylphosphoric acid were diluted with 20 parts of deionized water, added to the above Al2O3 dispersion, and the pH value of the solution was just 3, and vigorously stirred for 5 min. 4 parts of ferric chloride were dissolved in 30 parts of deionized water to prepare a solution, and then added to the above dispersion, and slowly stirred at a uniform speed for 1 h to make it uniformly coated. Vacuum filtration, washing, and drying at 60°C for 24 h to obtain spherical Al2O3 coated with an organic layer.
[0022] Preparation of anhydride ethylene propylene diene monomer rubber 100 parts of EPDM were added into an internal mixer at 170°C and 60 r / min for 3 min, and then 2.5 parts of maleic anhydride and 0.1 parts of diisopropylbenzene peroxide (DCP) were added into the EPDM and mixed evenly. The reaction was continued for 9 min, and finally 2 parts of zinc acetate were added and internally mixed for 3 min. The product was taken out and cooled to room temperature to obtain anhydride EPDM.
[0023] Preparation of high thermal conductivity EPDM rubber composites 100 parts of anhydride EPDM were added to a two-roll mill and mixed at room temperature. After 5 minutes, modified spherical alumina was added and mixed for 15 minutes. Then, it was transferred to an internal mixer, 100 parts of waste rubber powder (WRP) was added and mixed at 150℃ and 60 r / min for 5 minutes, and then 2 parts of carbon nanotubes (CNTs) were added and mixed for 10 minutes. Finally, it was hot-pressed at 150℃ and 15 MPa for 12 minutes to obtain a high thermal conductivity EPDM composite material mediated by alumina interfacial crosslinking and rubber powder volume exclusion. According to the test, the tensile strength of the EPDM composite material is 1.38 MPa, the elongation at break is 263%, and the thermal conductivity is 1.82 W / mK. Example
[0024] Surface organic layer coating of spherical alumina 25 parts of spherical aluminum oxide (Al2O3) were added to 350 parts of a mixed solution of deionized water and isopropanol with a volume ratio of 7:3, and ultrasonicated for 1 h to make it uniformly dispersed, and then continuously mechanically stirred at a uniform speed. 3 parts of acryloyl isopropyl phosphate were diluted with 30 parts of deionized water, added to the above Al2O3 dispersion, and the pH value of the solution was just 3, and vigorously stirred for 5 min. 6 parts of ferric sulfate were dissolved in 60 parts of deionized water to prepare a solution, and then added to the above dispersion, and stirred slowly at a uniform speed for 1 hour to make it uniformly coated. Vacuum filtration, washing, and drying at 60°C for 24 h to obtain spherical Al2O3 coated with an organic layer.
[0025] Preparation of anhydride ethylene propylene diene monomer rubber 100 parts of EPDM were added into an internal mixer at 170°C and 60 r / min for 3 min. Then 3 parts of succinic anhydride and 0.1 parts of diisopropylbenzene peroxide (DCP) were added into the EPDM and mixed evenly. The reaction was continued for 13 min. Finally, 2 parts of zinc acetate were added and internal mixer was performed for 3 min. The product was taken out and cooled to room temperature to obtain anhydride EPDM.
[0026] Preparation of high thermal conductivity EPDM rubber composites 100 parts of anhydride EPDM were added to a two-roll mill and mixed at room temperature. After 5 minutes, modified spherical alumina was added and mixed for 15 minutes. Then, it was transferred to an internal mixer and 100 parts of waste rubber powder (WRP) were added and mixed at 150°C and 60 r / min for 5 minutes. Then, 2 parts of carbon nanotubes (CNTs) were added and mixed for 10 minutes. Finally, it was hot-pressed at 150°C and 15 MPa for 12 minutes to obtain a high thermal conductivity EPDM composite material mediated by alumina interfacial crosslinking and rubber powder volume exclusion. According to the test, the tensile strength of the EPDM composite material was 1.46 MPa, the elongation at break was 247%, and the thermal conductivity was 2.20 W / mK. Example
[0027] Surface organic layer coating of spherical alumina 25 parts of spherical aluminum oxide (Al2O3) were added to 350 parts of a mixed solution of deionized water and isopropanol in a volume ratio of 7:3, and ultrasonicated for 1 h to make it uniformly dispersed, and then continuously mechanically stirred at a uniform speed. 3 parts of propyl phosphoric acid were diluted with 30 parts of deionized water, added to the above Al2O3 dispersion, and the pH value of the solution was just 3, and stirred vigorously for 5 min. 6 parts of ferric sulfate were dissolved in 60 parts of deionized water to prepare a solution, and then added to the above dispersion, and stirred slowly at a uniform speed for 1 h to make it uniformly coated. Vacuum filtration, washing, and drying at 60°C for 24 h to obtain spherical Al2O3 coated with an organic layer.
[0028] Preparation of anhydride ethylene propylene diene monomer rubber 100 parts of EPDM were added into an internal mixer at 170°C and 60 r / min for 3 min, then 2 parts of itaconic anhydride and 0.1 parts of diisopropylbenzene peroxide (DCP) were added into the EPDM and mixed evenly, and the reaction was continued for 13 min. Finally, 2 parts of zinc acetate were added and internal mixer was performed for 3 min. The product was taken out and cooled to room temperature to obtain anhydride EPDM.
[0029] Preparation of high thermal conductivity EPDM rubber composites 100 parts of anhydride EPDM were added to a two-roll mill and mixed at room temperature. After 5 minutes, modified spherical alumina was added and mixed for 15 minutes. Then it was transferred to an internal mixer, 100 parts of waste rubber powder (WRP) were added and mixed at 150℃ and 60 r / min for 5 minutes, and then 1 part of carbon nanotubes (CNTs) was added and mixed for 10 minutes. Finally, it was hot-pressed at 150℃ and 15 MPa for 8 minutes to obtain a high thermal conductivity EPDM rubber composite mediated by alumina interfacial crosslinking and rubber powder volume exclusion. According to the test, the tensile strength of the EPDM rubber composite was 1.42MPa, the elongation at break was 266%, and the thermal conductivity was 1.65 W / mK. Example
[0030] Surface organic layer coating of spherical alumina 25 parts of spherical aluminum oxide (Al2O3) were added to 350 parts of a mixed solution of deionized water and isopropanol in a volume ratio of 7:3, and ultrasonicated for 1 h to make it uniformly dispersed, and then continuously mechanically stirred at a uniform speed. 3 parts of phytic acid were diluted with 30 parts of deionized water, added to the above Al2O3 dispersion, and the pH value of the solution was just 3, and vigorously stirred for 5 min. 6 parts of ferric sulfate were dissolved in 60 parts of deionized water to prepare a solution, and then added to the above dispersion, and slowly stirred at a uniform speed for 1 h to make it uniformly coated. Vacuum filtration, washing, and drying at 60°C for 24 h to obtain spherical Al2O3 coated with an organic layer.
[0031] Preparation of anhydride ethylene propylene diene monomer rubber 100 parts of EPDM were added into an internal mixer at 170°C and 60 r / min for 3 min, then 2 parts of itaconic anhydride and 0.1 parts of diisopropylbenzene peroxide (DCP) were added into the EPDM and mixed evenly, and the reaction was continued for 8 min. Finally, 2 parts of zinc acetate were added and internal mixer was performed for 3 min. The product was taken out and cooled to room temperature to obtain anhydride EPDM.
[0032] Preparation of high thermal conductivity EPDM rubber composites 100 parts of anhydride EPDM were added to a two-roll mill and mixed at room temperature. After 5 minutes, modified spherical alumina was added and mixed for 15 minutes. Then, it was transferred to an internal mixer, 100 parts of waste rubber powder (WRP) was added and mixed at 150°C and 60 r / min for 5 minutes, and then 4 parts of carbon nanotubes (CNTs) were added and mixed for 10 minutes. Finally, it was hot-pressed at 150°C and 15 MPa for 15 minutes to obtain a high thermal conductivity EPDM composite material mediated by alumina interfacial crosslinking and rubber powder volume exclusion. According to the test, the tensile strength of the EPDM composite material is 1.57MPa, the elongation at break is 230%, and the thermal conductivity is 1.86 W / mK. Example
[0033] Surface organic layer coating of spherical alumina 25 parts of spherical aluminum oxide (Al2O3) were added to 350 parts of a mixed solution of deionized water and isopropanol in a volume ratio of 7:3, and ultrasonicated for 1 h to make it uniformly dispersed, and then continuously mechanically stirred at a uniform speed. 3 parts of phytic acid were diluted with 30 parts of deionized water, added to the above Al2O3 dispersion, and the pH value of the solution was just 3, and vigorously stirred for 5 min. 6 parts of ferric sulfate were dissolved in 60 parts of deionized water to prepare a solution, and then added to the above dispersion, and slowly stirred at a uniform speed for 1 h to make it uniformly coated. Vacuum filtration, washing, and drying at 60°C for 24 h to obtain spherical Al2O3 coated with an organic layer.
[0034] Preparation of anhydride ethylene propylene diene monomer rubber 100 parts of EPDM were added into an internal mixer at 170°C and 60 r / min for 3 min, then 2 parts of itaconic anhydride and 0.1 parts of diisopropylbenzene peroxide (DCP) were added into the EPDM and mixed evenly, and the reaction was continued for 8 min. Finally, 2 parts of zinc acetate were added and internal mixer was performed for 3 min. The product was taken out and cooled to room temperature to obtain anhydride EPDM.
[0035] Preparation of high thermal conductivity EPDM rubber composites 100 parts of anhydride EPDM were added to a two-roll mill and mixed at room temperature. After 5 minutes, modified spherical alumina was added and mixed for 15 minutes. Then, it was transferred to an internal mixer, 100 parts of waste rubber powder (WRP) was added and mixed for 5 minutes at 150°C and 60 r / min, and 6 parts of carbon nanotubes (CNTs) were added and mixed for 10 minutes. Finally, it was hot-pressed at 150°C and 15 MPa for 16 minutes to obtain a high thermal conductivity EPDM composite material mediated by alumina interfacial crosslinking and rubber powder volume exclusion. According to the test, the tensile strength of the EPDM composite material is 1.73MPa, the elongation at break is 211%, and the thermal conductivity is 1.99 W / mK.
[0036] In summary, the addition of organic layer-coated spherical alumina, carbon nanotubes and waste rubber powder in the embodiment of the present invention has an enhancing effect on the mechanical properties and thermal conductivity of the anhydride-treated EPDM rubber, while also having high thermal conductivity while taking into account flexibility and elasticity.
[0037] The above embodiments describe the specific contents of the present invention in detail, but the present invention is not limited to the embodiments, and those skilled in the art can make equivalent substitutions, which should be included in the protection scope of the present invention.
Claims
1. A high thermal conductivity EPDM rubber composite material mediated by aluminum oxide interfacial crosslinking and rubber powder volume exclusion, characterized in that: The main raw materials of the rubber are composed of the following components, calculated by weight: EPDM 100 parts Waste Rubber Powder WRP 100-200 copies Spherical aluminum oxide Al2O3 10-25 parts Carbon nanotubes CNTs 1-6 parts 1-4 parts of organic phosphoric acid 2-6 parts of organic anhydride 2-6 parts of iron salt Wherein, the organic phosphoric acid is any one of phytic acid, propyl phosphoric acid, phenyl phosphoric acid, trimethyl phosphoric acid, and acryloyl isopropyl phosphoric acid; The organic acid anhydride is any one of itaconic anhydride, maleic anhydride and succinic anhydride; The iron salt is any one of ferric chloride, ferric sulfate and ferric nitrate.
2. A method for preparing a high thermal conductivity EPDM rubber composite material mediated by aluminum oxide interfacial crosslinking and rubber powder volume exclusion, characterized in that: Here’s how: S1: Surface organic layer coating of spherical aluminum oxide Add 10-25 parts of spherical aluminum oxide Al2O3 to 200-350 parts of a mixed solution of deionized water and isopropanol in a volume ratio of 7:3, and ultrasonicate for 1 hour to make it uniformly dispersed, and then continue to mechanically stir it at a uniform speed. Dilute 1-4 parts of organic phosphoric acid with 10-40 parts of deionized water, add it to the above Al2O3 dispersion, make the solution pH value just 3, and stir vigorously for 5 minutes; dissolve 2-6 parts of iron salt in 20-60 parts of deionized water to prepare a solution, add it to the above dispersion, and stir slowly at a uniform speed for 1 hour to make it uniformly coated; vacuum filter, wash, and dry at 60°C for 24 hours to obtain spherical Al2O3 coated with an organic layer; S2: Preparation of anhydride EPDM rubber 100 parts of EPDM were added into an internal mixer at 170°C and 60 r / min, and the mixture was mixed for 3 minutes. Then 2-6 parts of organic acid anhydride and 0.1 parts of dicumyl peroxide DCP were added into the EPDM and mixed evenly. The mixture was reacted for 5-15 minutes. Finally, 2 parts of zinc acetate were added, and the mixture was mixed for 3 minutes. The product was taken out and cooled to room temperature to obtain anhydride EPDM. S3: Preparation of high thermal conductivity EPDM rubber composites 100 parts of anhydride EPDM were added to a two-roll mill and mixed at room temperature. After 5 minutes, the modified spherical alumina prepared by S1 was added and mixed for 15 minutes. Then, it was transferred to an internal mixer and 100-200 parts of waste rubber powder WRP were added and mixed at 150°C and 60 r / min for 5 minutes. Then, 1-6 parts of carbon nanotubes CNTs were added and mixed for a further 10 minutes. Finally, it was hot pressed at 150°C and 15 MPa for 5-20 minutes to obtain a high thermal conductivity EPDM rubber composite material mediated by alumina interfacial crosslinking and rubber powder volume exclusion.
Citation Information
Patent Citations
A method for preparing insulating thermally conductive carbon fiber for thermal interface material
CN115704184B
Preparation method of filling type flexible organic silicon thermal interface material with high thermal conductivity and low contact thermal resistance
CN118772641A
Graphene thermal interface material as well as preparation method and application thereof
CN118978898A
Cited By
A thermally conductive gel, its preparation method and application
CN122563560A